Phenylephrine versus ephedrine on cerebral perfusion during carotid endarterectomy (PEPPER): study protocol for a randomized controlled trial - Pennekamp, Claire WA; Immink, Rogier V; Buhre, Wolfgang F; Moll, Frans L; de Borst, Gert Jan (Trials, 2013)
Background Intraoperative arterial hypotension can lead to severe complications in patients undergoing carotid endarterectomy, in particular if cerebral auto-regulation is impaired. Short-acting agents, such as phenylephrine or ephedrine, commonly used to correct intra-operative hypotension, have different hemodynamic effects. Recently, it was reported that, in healthy anesthetized subjects with intact cerebral auto-regulation, frontal lobe cerebral tissue oxygenation declined after phenylephrine bolus administration, while it was preserved after ephedrine use (Br J Anaesth 107:209–217, 2011; Neurocrit Care 12:17–23, 2010). However, the effect of both agents in patients undergoing carotid endarterectomy is unknown. The aim of this study is to assess the effect of two routinely used vasopressors (phenylephrine and ephedrine) on the cerebral hemodynamics during carotid endarterectomy. Methods/design Patients undergoing carotid endarterectomy will be prospectively included and randomized for correction of intraoperative hypotension with either phenylephrine (50 to 100 μg) or ephedrine (5 to 10 mg). If hypotension persists for more than five minutes after treatment, the patient will be classified as a non-responder and escape medication as preferred by the anesthesiologist will be administered. Changes in cerebral hemodynamics will be quantified by changes in transcranial Doppler-derived middle cerebral artery blood velocity and near infra-red spectroscopy-derived frontal lobe cerebral tissue oxygenation, when intra-operative hypotension is treated with phenylephrine or ephedrine in patients who undergo carotid endarterectomy with or without an adequate functioning cerebral auto-regulation. To quantify whether the intra-operative cerebral auto-regulation is impaired or not, a decrease in breathing frequency from the normal 12 breaths per minute to 6 breaths per minute for an episode of three minutes will be performed. Discussion Phenylephrine and ephedrine are two of the most commonly used short-acting agents to increase blood pressure in clinical anesthesiologic practice. Monitoring of middle cerebral artery blood velocity with transcranial Doppler and frontal lobe cerebral tissue oxygenation with near infra-red spectroscopy are part of the standard of care. Furthermore, there are no reports that the three-minute modification in breathing frequency described in the “intervention”-section is harmful. Therefore, the risks for participating patients are negligible and the burden minimal. Trial registration Clinical trials.gov: NCT01451294